2021
DOI: 10.3390/polym13152550
|View full text |Cite
|
Sign up to set email alerts
|

Combining Sandblasting, Alkaline Etching, and Collagen Immobilization to Promote Cell Growth on Biomedical Titanium Implants

Abstract: Our objective in this study was to promote the growth of bone cells on biomedical titanium (Ti) implant surfaces via surface modification involving sandblasting, alkaline etching, and type I collagen immobilization using the natural cross-linker genipin. The resulting surface was characterized in terms topography, roughness, wettability, and functional groups, respectively using field emission scanning electron microscopy, 3D profilometry, and attenuated total reflection-Fourier transform infrared spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that the abundant hydroxyl groups in procyanidin form hydrogen bonds with COL1 to achieve cross-linking without destroying the collagen structure ( He et al, 2011 ). Besides, genipin obtained from the fruit of Genipa Americana may be an alternative of natural crosslinking agents ( Liu et al, 2021 ). It is worth noting that the PDA-assisted bioinspired method can also be used to covalently immobilize with COL1 on Ti surfaces ( Zhao et al, 2022 ).…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
“…Previous studies have shown that the abundant hydroxyl groups in procyanidin form hydrogen bonds with COL1 to achieve cross-linking without destroying the collagen structure ( He et al, 2011 ). Besides, genipin obtained from the fruit of Genipa Americana may be an alternative of natural crosslinking agents ( Liu et al, 2021 ). It is worth noting that the PDA-assisted bioinspired method can also be used to covalently immobilize with COL1 on Ti surfaces ( Zhao et al, 2022 ).…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
“…However, excessive coating thickness may result in peeling. Some pretreatments, such as alkaline treatment, can effectively enhance the adhesion of subsequent coatings [138]. Heat treatment can ameliorate the stress state between different layers and strengthen the bonding, adopting a progressive design that optimizes each layer step-by-step to obtain a multifunctional composite coating with stable and controllable performance [139].…”
Section: Functional Composite Coatingsmentioning
confidence: 99%